The Influence of Service Quality on Satisfaction in Shaping Patient Loyalty Herlina Kasih Hospital Sorong - Rudianana, Rana; Veranita, Mira; Mustiraya, Raya (Journal of Social and Policy Issues, 2025)
This study aims to analyze the effect of service quality on patient satisfaction and its implications for loyalty at Herlina Kasih Hospital, a semi-urban health facility facing increasing competition. Service quality was examined comprehensively through the five SERVQUAL dimensions: tangibles, reliability, responsiveness, assurance, and empathy. A quantitative research approach was applied using purposive sampling, with 116 patients who had visited the hospital more than four times and were aged 16 years or older. Data were collected through structured questionnaires and analyzed using path analysis after passing classical assumption tests to ensure validity and reliability. The results show that all SERVQUAL dimensions significantly influence patient satisfaction, with empathy emerging as the most dominant factor. Furthermore, service quality has both direct and indirect effects on patient loyalty, where satisfaction acts as a significant mediating variable. This finding indicates that loyalty is not merely shaped by perceptions of service but is strongly determined by the level of patient satisfaction. The study concludes that improving hospital services requires a holistic, patient-centered approach that integrates personal interaction and technological innovation. By strengthening service quality across all dimensions, hospitals can enhance patient experiences, build long-term loyalty, and create a sustainable competitive advantage in the healthcare sector.